2020
DOI: 10.1136/jmedgenet-2020-106867
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-first in a cohort of 95 fetuses with multiple congenital abnormalities: when exome sequencing reveals unexpected fetal phenotype-genotype correlations

Abstract: PurposeMolecular diagnosis based on singleton exome sequencing (sES) is particularly challenging in fetuses with multiple congenital abnormalities (MCA). Indeed, some studies reveal a diagnostic yield of about 20%, far lower than in live birth individuals showing developmental abnormalities (30%), suggesting that standard analyses, based on the correlation between clinical hallmarks described in postnatal syndromic presentations and genotype, may underestimate the impact of the genetic variants identified in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
2
26
1
Order By: Relevance
“… 32 , 41‐48 , 33‐40 Eight studies targeted ES analysis more tightly using phenotype‐specific gene panels, 7 , 12 , 15 , 49‐53 while the remainder took a whole ES approach 8 ,. 13 , 62‐71 , 54 , 72‐81 , 55 , 82‐88 , 56‐61 Where stated (15 studies), 7 , 8 , 74 , 75 , 78 , 82 , 84 , 15 , 29 , 36 , 52 , 53 , 55 , 62 , 73 the median turnaround time for ES was 20 days (range 4–141). Studies included fetuses with a range of structural abnormality phenotypes, with some studies recruiting cases with fetal anomalies in a specific body system (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 , 41‐48 , 33‐40 Eight studies targeted ES analysis more tightly using phenotype‐specific gene panels, 7 , 12 , 15 , 49‐53 while the remainder took a whole ES approach 8 ,. 13 , 62‐71 , 54 , 72‐81 , 55 , 82‐88 , 56‐61 Where stated (15 studies), 7 , 8 , 74 , 75 , 78 , 82 , 84 , 15 , 29 , 36 , 52 , 53 , 55 , 62 , 73 the median turnaround time for ES was 20 days (range 4–141). Studies included fetuses with a range of structural abnormality phenotypes, with some studies recruiting cases with fetal anomalies in a specific body system (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…14,32,[41][42][43][44][45][46][47][48][33][34][35][36][37][38][39][40] Eight studies targeted ES analysis more tightly using phenotypespecific gene panels, 7,12,15,[49][50][51][52][53] while the remainder took a whole ES approach. 8,13,[62][63][64][65][66][67][68][69][70][71]54,[72][73][74][75][76][77][78][79][80][81]55,[82][83]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For the quantitative analysis, 40 articles [121, were secondarily excluded. Of these, three papers focused on fetal demises or stillbirths [256][257][258], three papers focused on information postmortem [242,250,254], three were case reports [238,246,252], five focused on a single specific phenotype [240,241,248,261,274], three presented inhomogeneity in inclusion criteria and chromosomal anomalies/CNV assessment [239,251,262], six included both fetuses and postnatal cases [244,249,253,259,260,269], three focused on candidate genes [243,247,263], three focused on recurrent phenotypes or previously described cohorts [245,255,272], five were excluded for the lack of inclusion or eligibility criteria [264,265,268,271,276], two were excluded for the higher a priori risk for consanguinity and recurrence [266,270], one because parents were tested for recessive disorders [267], two because they focused on gene panels [273,275], and one due to the postnatal diagnosis [121].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…Two of the largest cohort studies on prenatal WES to date found similar diagnostic yields of approximately 10% in pregnancies complicated by fetal structural anomalies but with normal karyotype and microarray 1,2 . Other studies reported even higher yields 3–5 . Pregnancy complicated by multiple fetal anomalies is associated with the highest yield for diagnostic genetic variants followed by skeletal anomalies and non‐immune hydrops fetalis 1–3,6 .…”
Section: Introductionmentioning
confidence: 98%
“…1,2 Other studies reported even higher yields. [3][4][5] Pregnancy complicated by multiple fetal anomalies is associated with the highest yield for diagnostic genetic variants followed by skeletal anomalies and non-immune hydrops fetalis. [1][2][3]6 WGS and WES have not been adopted into routine practice in obstetric care due to high cost and suspected low diagnostic yield above karyotype and microarray.…”
Section: Introductionmentioning
confidence: 99%